Edukasi Deteksi Dini Diabetes Melitus Kader Puskesmas Pondok Kacang Timur Tangerang Selatan - Zahra Nurusshofa; Alzafan Efraim Notatema Gori; Regita Almira Claudia (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The number of Diabetes Mellitus (DM) patients in the world is continuing to increase. Initially, in 1980, there were only 108 million patients, which increased to 422 million individuals in 2014. The number of incidences is increasing disproportionately in countries with middle and low incomes compared to high-income countries. Mortality caused by diabetes mellitus occurs in 20.9 people per 100,000 of the country's population. Several causes of the high incidence of mortality caused by DM, include delays in determining a diagnosis and non-adherence to treatment. Health center cadres are an extension of the puskesmas in reaching out to the community in the working area of each public health center. Based on this context, this activity aimed to educate health center cadres in regard to early detection of DM and complications related to DM in order that they can educate the public and motivate them to cooperate in the treatment of DM. After the education program was implemented, an increase in knowledge about DM was found among health center cadres. This finding was determined by looking at the mean score, which increased from 74.8 during the pretest to 84.4 during the post-test.